Crispr Cas – Revolutionizing Modern Therapies and Beyond - Samiddha Banerjee (International Journal of Genetic Modifications and Recombinations, 2025)
CRISPR-Cas technology has emerged as a transformative tool in modern molecular biology, revolutionizing both fundamental research and clinical applications. This RNA-guided gene-editing system enables precise and efficient genomic modifications, offering unprecedented potential for addressing genetic disorders, infectious diseases, and oncological conditions through innovative therapeutic interventions. The inherent specificity and programmability of CRISPR-Cas systems have facilitated breakthroughs in diverse fields, including precision medicine, regenerative therapies, and immuno-oncology. Beyond its therapeutic applications, CRISPR-Cas technology plays a critical role in agricultural biotechnology, environmental remediation, and synthetic biology, enabling the development of genetically modified organisms with improved traits, biosensors for pathogen detection, and novel bioengineered systems for sustainable bio-production. The ability to introduce targeted modifications at single-nucleotide resolution has expanded the frontiers of functional genomics, allowing researchers to systematically investigate gene function, regulatory networks, and epigenetic modifications with unprecedented accuracy. In contemporary medical therapies, CRISPR-Cas-based approaches are being explored for correcting monogenic disorders, engineering immune cells for adoptive cell therapies, and developing novel strategies for viral disease eradication. CRISPR-based diagnostic tools have also been harnessed for rapid, cost-effective detection of pathogenic infections and cancer biomarkers, paving the way for early disease intervention and personalized treatment regimens. Furthermore, theranostic applications integrating CRISPR-Cas technology with advanced imaging modalities are poised to enhance precision medicine by enabling simultaneous disease diagnosis and targeted therapeutic delivery. This article delves into the extensive impact of CRISPR-Cas systems on modern therapeutic paradigms, particularly in the fields of molecular diagnostics, targeted cancer therapies, and antiviral theranostics. Additionally, it examines the broader implications of this revolutionary technology for future biomedical research, ethical considerations, and translational medicine.
Keywords: CRISPR-Cas; gRNA; immuno-oncology; molecular scissors